Is the calcite–water interface understood?: Direct comparisons of molecular dynamics simulations with specular x-ray reflectivity data - Fenter, P.; Kerisit, S.; Raiteri, Paolo; Gale, Julian (American Chemical Society, 2012)
New insights into the understanding of calcite-water interface structure are obtained through direct comparisons of multiple classical molecular dynamics (MD) simulations with high-resolution specular X-ray reflectivity (XR) data. This set of comparisons, with four different state of-the-art force fields (including two non-polarizable, one polarizable, and one reactive force field), reveal new insights into the absolute accuracy of the simulated structures and the uniqueness of the XR-derived structural results. These four simulations, though qualitatively similar, have visibly distinct interfacial structures and are distinguished through a quantitative comparison of the XR signals calculated from these simulations with experimental XR data. The results demonstrate that the simulated calcite-water interface structures, taken as a whole, are not consistent with the XR data (i.e., within the precision and accuracy of the XR data). This disagreement is largely due to the simulated calcite interfacial structure. The simulated interfacial water profiles show a higher level of consistency with the XR data, but with substantially different levels of agreement, with the rigid-ion model (RIM) simulations showing semi-quantitative agreement. Further comparisons of the structural parameters that describe the interfacial structure (derived from both the MD simulations and the XR data) provide further insight into the sources of differences between these two approaches. Using the new insights from the RIM simulations, new structures of the calcite-water interface consistent with both the experimental data and the simulation are identified and compared to recent results.